Plan Your Own Estate Passing on Your Assets and Your Values Legally and Efficiently - Wheatley-Liss, Deirdre R. (Apress : Imprint: Apress, 2013)
Plan Your Own Estate: Passing on Your Assets and Your Values Legally and Efficiently takes a straightforward and engaging ́ƠSyoúƠý-oriented approach to dealing with one of liféƠ"s certainties--death. While you "cańƠ"t take it with you," this book empowers you to decide how your assets can best help your family when you are gone. Experienced attorney Deirdre R. Wheatley-Liss concentrates into this book the experience she's had helping hundreds of families work through their estate plans. Whether you have modest or extensive assets, Plan Your Own Estate provides the knowledge you need to design your plan and the tools you need to move forward. The starting place is your goals. Part 1 of the book asks, "What do you want to accomplish for yourself and your family?" The next step depends on you. Are you looking to educate yourself about how a will or trust is structured, or how tax law works? Part 2, Resource Guides, breaks down tough topics like these and delivers actionable information. Have questions about what your estate plan should say? Part 3, Planning Guides, goes through an attorneýƠ"s analysis in considering the most frequently asked estate planning questions. Thinking about creating your own estate plan, or hiring an attorney? Part 4, Action Guides, helps you start your estate plan and make sure it́Ơ"s complete, or review any plan you may already have in place.  Nobody likes talking about death, taxes, or disability--but not thinking about them will not make them go away. Plan Your Own Estate will help you make a plan, put it in place, and take control of how your money and your values are being passed to your family. This book includes: Comprehensive ́ƠSplain English́Ơý coverage of every aspect of planning your estate Methods to protect your loved ones' inheritance from taxes, immaturity, lack of financial knowledge, incapacity, creditors, and predators Planning guides for families with children, singles, second marriages, business owners, unmarried or same-sex couples, and more Up-to-date information regarding changing laws and best practices.